Role of sex hormones in diabetic nephropathy - Liu, Jiahui; Liu, Zhe; Sun, Weixia; Luo, Ling; An, Xingna; Yu, Dehai; Wang, Wanning (Frontiers in Endocrinology, 2023)
Diabetic nephropathy (DN) is the most common microvascular complication in diabetes and one of the leading causes of end-stage renal disease. The standard treatments for patients with classic DN focus on blood glucose and blood pressure control, but these treatments can only slow the progression of DN instead of stopping or reversing the disease. In recent years, new drugs targeting the pathological mechanisms of DN (e.g., blocking oxidative stress or inflammation) have emerged, and new therapeutic strategies targeting pathological mechanisms are gaining increasing attention. A growing number of epidemiological and clinical studies suggest that sex hormones play an important role in the onset and progression of DN. Testosterone is the main sex hormone in males and is thought to accelerate the occurrence and progression of DN. Estrogen is the main sex hormone in females and is thought to have renoprotective effects. However, the underlying molecular mechanism by which sex hormones regulate DN has not been fully elucidated and summarized. This review aims to summarize the correlation between sex hormones and DN and evaluate the value of hormonotherapy in DN.